The normal and the painful shoulders during the breaststroke - Ruwe, P. A.; Pink, M.; Jobe, F. W.; Perry, J.; Scovazzo, M. L. (The American Journal of Sports Medicine, 1994)
Electrical activity in 12 shoulder muscles during breaststroke were compared in 25 swimmers, 14 of whom had painful shoulders. Electrical activity was increased in the internal rotator muscles in swimmers with painful shoulders. Also activity was decreased in the teres minor, supraspinatus, and upper trapezius muscles. These factors increase the risk of impingement. The muscles that performed the greatest work in normal-shoulder swimmers were the serratus anterior and teres minor. They are also likely to be those most fatigued. It was recommended that specific muscle training of an endurance nature for the serratus anterior and teres minor and that the functioning of the internal and external rotators of the shoulder should be balanced during the stroke to avoid impingement. Implication: Excessive use of the internal rotator muscles, generally those in front of the shoulder, will lead to shoulder problems in breaststroke and indeed all strokes. If prolonged enough the pull of those muscles articulates the head of the humerus forward to cause impingement resulting in pain and chronic problems. Some attempt should be made to have swimmers feel that they are using their "back" muscles (i.e., back of the shoulder) during the breaststroke pull and recovery as a way of producing a "balanced" pull and avoiding impingement.